Pengaruh Perlakuan Alkali Terhadap Kekuatan Tarik Bahan Komposit Serat Rumput Teki - Zian Millenio; Fajar Paundra; H.T. Yudhistira; E. Pujiyulianto; Imam Prabowo (Journal of Applied Mechanical Technology, 2022)
Composite is a combination of two or more materials with different characteristics into a single unit. This study aims to determine the effect of immersion time of alkali (NaOH) on the tensile strength of composites reinforced teki grass. The alkaline immersion process was carried out with variations of 0 hours, 2 hours, 4 hours, and 6 hours with an alkali concentration of 5%. Tensile test using ASTM D3039 standard. The lowest tensile test results occurred in the 0-hour immersion variation of 4.15 MPa, while the highest tensile strength value occurred in the 4-hour immersion variation of 21.72 MPa.